Linking fossil reefs with earthquakes: Geologic insight to where induced seismicity occurs in Alberta. Issue 6 (24th March 2016) - Schultz, Ryan; Corlett, Hilary; Haug, Kristine; Kocon, Ken; MacCormack, Kelsey; Stern, Virginia; Shipman, Todd
Abstract: Recently, a significant increase in North American, midcontinent earthquakes has been associated with contemporaneous development of petroleum resources. Despite the proliferation of drilling throughout sedimentary basins worldwide, earthquakes are only induced at a small fraction of wells. In this study, we focus on cases of induced seismicity where high‐resolution data are available in the central Western Canada Sedimentary Basin. Our regional comparison of induced earthquake depths suggests basement‐controlled tectonics. Complementary to these findings, hypocenters of induced seismicity clusters coincide with the margins of Devonian carbonate reefs. We interpret this spatial correspondence as the result of geographically biased activation potential, possibly as a consequence of reef nucleation preference to paleobathymetric highs associated with Precambrian basement tectonics. This finding demonstrates the importance of geologic/tectonic factors to earthquake induction, in addition to industrial operational parameters. In fact, the observation of induced seismicity silhouetting deep fossil reef systems may be a useful tool to identify future regions with increased seismogenic potential. Key Points: Induced seismicity in Alberta is spatially correlated to a geological formation This spatial correlation is highly unlikely to be coincidental Correlation is interpreted as a result of geologically biased activation potential